How parent-adolescent conflict in different domains predict academic performance in early adolescence? - Brković, Irma; Puklek Levpušček, Melita; Keresteš, Gordana (2013)
Increase in parent-adolescent conflict and decrease in academic performance are well established changes in early adolescence. However, there is little empirical work linking these two changes. The aim of this study was to explore changes in academic performance over a five-year period among Croatian early adolescents and to link these changes with parent-adolescent conflicts in four domains: school and homework, home chores, free time and moral issues. Gender differences in changes in academic performance were also examined. We applied accelerated approach to overlapping cohort design in which 851 adolescents (51.4% girls) and 1288 parents (53.9% mothers) took part in three data-collection occasions. Multilevel longitudinal modeling allowed us to calculate developmental trajectories for five-year period of early adolescence, as well as to compare if and how various topics of parent- adolescent conflict contribute to prediction of academic achievement. Parallel forms of the Parent-Adolescent Conflict Scale were administered to measure parent-adolescent conflict in different dyads and from different informants. Average midterm school grade was used as an indicator of academic achievement. The results showed an overall decrease in academic achievement, steeper among boys and at the beginning of early adolescence. Conflicts in all four domains were related to school achievement. However, when other factors were controlled for, conflicts related to free time could not predict school achievement, while school-, home- and moral-related conflicts all kept independent predictive validity, with school-related conflicts being the strongest predictor of school achievement.
Projekt MZOS
ENG